At IIHR, Bengaluru... Floricultural research and development - Janakiram, T (Indian Horticulture, 2019)
Floriculture has been identified has a sunrise industry by the Government of India, having immense potential for generating gainful self-employment among small and marginal farmers. Recently, it has emerged as a profitable agribusiness in India and worldwide, improving standard of living and growing consciousness among the citizens across the globe to live in an environmentfriendly atmosphere. The production and trade of floriculture has increased consistently over the last 10 years. In India, floriculture industry comprises flower trade, production of nursery plants and potted plants, seed and bulb production, micropropagation and extraction of essential oils. Though the annual domestic demand for the flowers is growing at a rate of over 25% and international demand at around ` 90,000 crores.